KINERJA SEKDES PNS DI KECAMATAN SAWIT KABUPATEN BOYOLALI (KAJIAN DI DESA CEPOKOSAWIT DAN DESA GOMBANG - Sri Purnama Sari; Yuwanto .; Rina Martini (Journal of Politic and Government Studies, 2015)
The implementation of the village administration takes the role of villageofficials, as well as the secretary of the village in the Sawit district of Boyolali is areliable, professionalism and competent in their fields of a village secretary.Theappointment of the secretary of the village was being expected to motivate othervillage officials, who is not being civil servants to be more active, whilethe secretaryof the village carry out their duties and functions. Therefore, the formulation of theproblem in this research is "How to know the performance of the village secretary inSawit district of Boyolali?".This study aims to determine the performance of the village secretary in theCepokosawit and Gombangvillage, which located in the area of Sawit District ofBoyolali. Theuse of method in this research is descriptive qualitative. The primarydata source was obtained through interviews, and secondary data from documents,archives, other sources were associated with this research. This research usingqualitative data analysis techniques with analysis in the form of description,depiction and conclusion on the symptoms studied.The researchshows the performance of the village secretaryin the Sawitdistrict of Boyolali in terms of the government organization that emphasizesteamwork, discipline, creativity, prosperity of society, and responsibility for thewelfare. The indicators of cooperation and creativity in the Cepokosawit andGombang village. remains low, the village secretary can not be able to establish agood cooperation with other village officials and just wait the command from thevillage secretary to carry out their duties. While the indicators of discipline andresponsibility had a slight change. As an examplethe village secretary is tocome andgo in accordance with the rule of hours 08.00 pm until 14.00 pm, it is quite differentbefore he is not being civil servants who was tend to come and go as they pleasedfrom offices. Previously, the village secretary responsibility only finished to thevillage head, but now the responsibility is also to the head district and regent.Adviceamong others can be givento improve the ability of the secretary ofthe village, who is to perform their duties must master in the field of IT, includingthe Internet. The secretary of the village as civil servants should be able to give agood example and motivation for the other village officials in order to work hardermore optimal, more professionals, especially to provide public services.Keywords: Performance, Village Secretary of civil servants , cooperation,discipline, creativity, responsibility.